On – and in – bicultural encounter. (3rd April 2022) - Rivers, Shirley; Rodgers, Brian; May, Janet; Tudor, Keith
ABSTRACT: This article tells a story of bicultural engagement in Aotearoa New Zealand, specifically in the context of offering a space – and place – for engagement in and discussion about relationships between tangata whenua, the first people of the land of Aotearoa New Zealand, and subsequent settlers. Framed in terms of relational engagement (in)formed by contact, connection, journey and place, the article welcomes the reader, and introduces the authors and their relationship(s) to and with bicultural encounter. Drawing on the image of the double-hulled waka, a sea-going voyaging canoe, the article discusses encounter and biculturalism. We finish with some vignettes and reflections around our experience of bicultural encounter in the context of the PCE2021 conference.